1997
DOI: 10.2172/552792
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of waste tank passive ventilation rates using tracer gases

Abstract: This report presents the results of ventilation rate studies of eight passively ventilated high-level radioactive waste tanks using tracer gases. Headspace ventilation rates were determined for Tanks A-101, AX-102, AX-103, BY-105, C-107, S-102, U-1 03, and U-105 using sulfur hexafluoride (SF,) and/or helium (He) as tracer gases. Passive ventilation rates are needed for the resolution of several key safety issues. These safety issues are associated with the rates of flammable gas production and ventilation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 7 publications
2
42
0
Order By: Relevance
“…Only a single estimate of breathing rate based on tracer gas studies is usually available for most tanks (Huckaby et al 1997). That estimate may be based on the average of multiple measurements taken over a number of different days, but usually the data do not span the seasonal variation of ventilation.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Only a single estimate of breathing rate based on tracer gas studies is usually available for most tanks (Huckaby et al 1997). That estimate may be based on the average of multiple measurements taken over a number of different days, but usually the data do not span the seasonal variation of ventilation.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…(Ventilation rates in DCRTs are currently being measured, and the results will be incorporated into future versions of this document.) This "administrative" ventilation is significantly less than even the 2-15 scfm passive ventilation rates that have been measured in SSTs (Huckaby et al 1997). Because of this limited ventilation, flammable gas concentrations in DCRTs are often calculated to be significantly higher than they are in SSTs, where under normal circumstances those gases are at concentrations well below the level of concern.…”
Section: Dcrtsmentioning
confidence: 95%
“…Huckaby et al (1997) found that mixing times in S-102 (an SST) were about one hour, apparently because of natural convection. The TEMPEST modeling of the same tank (Antoniak and Recknagle 1997) was in agreement with the observations.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Gas tracer studies have been conducted to determine the passive ventilation rates of U-102, U-103, U-105, U-106, and U-111 over periods of one to two months (Huckaby et al 1997 the U-farm tanks range from 1.3 to 5.2 ft 3 /min with an average of 2.5 ft 3 /min. The tracer tests on S-102 showed a range of 1.2 to 3.4 scfm with an average of 2.1 scfm.…”
Section: Estimated Ventilation Ratesmentioning
confidence: 99%